2019
DOI: 10.1002/lio2.258
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of total parotidectomy defects with a de‐epithelialized submental flap

Abstract: Objective Total parotidectomy yields a large surgical defect that leads to both cosmetic and functional deficits which can be addressed with reconstruction. We evaluated the role of a pedicled submental flap for this reconstruction. Methods We reviewed all submental flap reconstructions that were performed for total parotidectomy defects between 2014 and 2016. Data regarding harvest technique, postoperative complications, flap survival, and adjuvant treatment details we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The most successful methods at preventing FS are temporoparietal fascial flaps, acellular dermal matrices and free fat grafts, with more traditional techniques such as the sternocleidomastoid and superficial musculoaponeurotic system flaps proving less efficient barrier techniques 38 . Recently, a new technique involving a de‐epithelialized sub mental flap has been recommended for reconstruction of parotidectomy defects but has not yet been tested as a method to prevent FS 39 . It could be suggested that creating a physical barrier reduces the incidence of aberrant regeneration by blocking the growth of parasympathetic neurons toward sweat glands.…”
Section: Discussion and Future Developmentsmentioning
confidence: 99%
“…The most successful methods at preventing FS are temporoparietal fascial flaps, acellular dermal matrices and free fat grafts, with more traditional techniques such as the sternocleidomastoid and superficial musculoaponeurotic system flaps proving less efficient barrier techniques 38 . Recently, a new technique involving a de‐epithelialized sub mental flap has been recommended for reconstruction of parotidectomy defects but has not yet been tested as a method to prevent FS 39 . It could be suggested that creating a physical barrier reduces the incidence of aberrant regeneration by blocking the growth of parasympathetic neurons toward sweat glands.…”
Section: Discussion and Future Developmentsmentioning
confidence: 99%
“…There are several common locoregional options for relatively small defects including acellular dermis, sternocleidomastoid (SCM) muscle flap, and local fascia flaps [ 5 ]. Other reported regional options include both the submental flap [ 3 ] and submandibular gland (SMG) flap [ 2 ]. In addition, fat grafting is also frequently used but requires an additional operative site.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate volume loss over time, larger defects require more vascularized flaps. Pedicled flaps, such as the sternocleidomastoid (SCM) muscle flap, supraclavicular artery flap, and submental flap, and for even larger defects, autologous free tissue flaps, may be required [ 2 , 3 ]. Local pedicled flaps, however, can provide some advantages over utilization of free flaps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The submental artery island flap (SAIF) is a wellestablished reconstructive option for defects of the head and neck; commonly utilized for the oral cavity, temporal bone, parotid, or skin. [1][2][3][4] While free tissue transfer remains the workhorse for reconstructing large defects of the head and neck, the SAIF has demonstrated value for a variety of reconstructive challenges. In comparison with free flaps, the SAIF offers lower procedural time and hospital length of stay (LOS).…”
Section: Introductionmentioning
confidence: 99%